2018
DOI: 10.1016/j.injury.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Polytrauma patients in the Netherlands and the USA: A bi-institutional comparison of processes and outcomes of care

Abstract: Although several outcome parameters differ in two urban area trauma centers in the USA and the Netherlands, the quality of care for trauma patients, measured as survival, is equal. Other outcomes varied between both trauma centers, suggesting that differences in local policies and processes do influence the care system, but not so much the quality of care as reflected by survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…11 Trauma was commonest between young males because they always participate in high-risk activities, with highspeed driving and also drive without wearing any protective tools. 18 Regarding to the mechanism of injury, this study showed that the majority of the studied patient had motor car crash (55.30%), while motor cycle crash was the second mechanism of trauma (21.40%), run over was the third This agrees with several studies conducted on trauma epidemiology, where the majority of cases were due to road side collisions. Payal et al had found that 72% (n=150) were due to road side accidents, followed by fall from height 15% (n=31).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…11 Trauma was commonest between young males because they always participate in high-risk activities, with highspeed driving and also drive without wearing any protective tools. 18 Regarding to the mechanism of injury, this study showed that the majority of the studied patient had motor car crash (55.30%), while motor cycle crash was the second mechanism of trauma (21.40%), run over was the third This agrees with several studies conducted on trauma epidemiology, where the majority of cases were due to road side collisions. Payal et al had found that 72% (n=150) were due to road side accidents, followed by fall from height 15% (n=31).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the outcome of patients in the Our study showed (18.4%) mortality rate ( Figure 1) which higher than Pfeifer et al, in which mortality rate in polytrauma patients (6.4%) and also higher than Mica et al, in which mortality rate was (9.6%) and in Dijkink et al study mortality rate (10%). 1,[16][17][18] Higher mortality rate of our study maybe due to we compare with specialized trauma center which highly prepared and about ICU admission, our study showed (44.7%) ( Figure 1) which agree with Dijkink et al, in which ICU admission percentage (47.3%). 18 The study demonstrated a need to improve overall ATLS compliance at our institution.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The innate immune response after severe tissue trauma or life-threatening multiple injury (polytrauma) results in a multi-faceted systemic disease with a complex and heterogeneous, although mainly compartmentalized, response 68 . To cover the organ systems most frequently affected by severe trauma—the head, chest and abdomen (in descending prevalence) 9,10 —this Review addresses mainly those systems, plus the endothelium as a ‘meta-organ’, and their interrelated changes in innate immunity after trauma.…”
mentioning
confidence: 99%
“…rauma is one of the major causes of death in people aged under 46 years in the United States (Rees et al 2015), Japan (Nagata et al 2018), and South Africa (Moller et al 2018). The quality of care for patients with trauma affects their survival rate (Dijkink et al 2018). Appropriate education can help students identify threats to patient's safety in trauma situations (Cohen et al 2018).…”
Section: Introductionmentioning
confidence: 99%